EFFECT OF INSULIN ON PROGESTERONE PROFILE AND CONCEPTION RATE IN CROSSBRED COWS - SHARMA, MRIDULA; GUPTA, H P; PRASAD, SHIV; AGARWAL, SANJAY (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on 48 crossbred cows aged 4-12 years, divided into four groups (n=12in each group). In I, II and Ill (Treated) groups, insulin@ 0.25 IU/Kg (Human Mixtard®, Torrent PharmaceuticalsLtd., India) was given subcutaneously daily for 4 days on days 0-3, 4-7 and 8-11 of estrous cycle, respectivelyand in control group PBS (s/c) was administered comparable to insulin suspension on 4-7 days of estrouscycle. Blood samples were collected on day 0, 5, 10, 16 and 21 and serum was separated for estimation ofprogesterone (P4). Serum P4 concentration on day 10 and 16 was significantly (P
Keywords: Insulin; Progesterone; Conception rate; Crossbred cows